Sastra Arab di Asia Tenggara: Studi Kasus di Indonesia - Azizah, Balkis Nur (Program Studi Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Raden Fatah Palembang, 2023)
This article aims to: (1) find out the entry of Arabic literature in Indonesia; (2) describe the types of Arabic literature in Indonesia; (3) describe literary figures in Indonesia; (4) the influence of Arabic literature in Indonesia. The writing is collected by conducting a library search, searching for relevant sources, and searching for data through the internet. The data and information used are books, journals, theses, electronic media, and several relevant libraries. The results of this paper indicate that (1) Arabic literature is estimated to have entered Indonesia in the 18th century AD through Arab traders, but some argue that Arabic literature came along with the entry of Islam into Indonesia; (2) the types of Arabic literature that exist in Indonesia are poetry, old and new prose, as well as translations; (3) in Indonesia, there are literary figures such as Halimi Zuhdy and translator figures such as Ali Audah; (4) while Arabic literature contributes significantly to Indonesian and Malay literature.